Speaking Anxiety Among Indonesian Undergraduate Students in Argumentative Speaking Classes - Apriliano Jarot Prayogo, Edo; Halwat Hikmat, Mauly (Universitas Negeri Semarang, 2024)
The aims of this research are: (1) to determine the level of speaking anxiety among Indonesian undergraduate students, especially in argumentative speaking classes; (2) to identify factors that influence students' speaking anxiety in argumentative speaking classes; and (3) to explore students' strategies for overcoming their speaking anxiety in argumentative speaking classes. This research was conducted at Universitas Muhammadiyah Surakarta. The participants were 3rd-semester students of the English Language Education Department. The research method used in this research is qualitative descriptive. Data collection was carried out through the Foreign Language Class Anxiety Scale (FLCAS) questionnaire from (Horwitz, 1986) in (Zhang, 2024), and interviews. To obtain data validity, researchers applied methodological triangulation. Next, the qualitative data was analyzed using the model proposed by Miles and Huberman in (Purbaya et al., 2024) with the following steps: data collection, data reduction, data presentation, and drawing conclusion. The research revealed that: (1) 48% of students suffer from moderate levels of anxiety, namely students become nervous or restless when their speaking ability seems hampered, (2) 6 factors cause speaking anxiety in students, namely; level of English proficiency, fear of making mistake, low self-esteem, lack of preparation, motivation, learning techniques; and (3) students use four effective strategies such as preparation, relaxation, positive thinking, peer-seeking strategy to overcome their anxious feelings.